Cyclic plasticity and creep of power plant materials - Saad, Abdullah Aziz (2012)
The thermo-mechanical fatigue (TMF) of power plant components is caused by the cyclic operation of power plant due to startup and shutdown processes and due to the fluctuation of demand in daily operation. Thus, a time-dependent plasticity model is required in order to simulate the component response under cyclic thermo-mechanical loading. The overall aim behind this study is to develop a material constitutive model, which can predict the creep and cyclic loading behaviour at high temperature environment, based on the cyclic loading test data of the P91 and the P92 steels.